Value Chain Analysis of Korarima (Aframomum Corrorima) in South Omo Zone, SNNPR Ethiopia - Adicha, Asmera; Alemayehu, Yidnekachew; Ermias, Gedion; Darcho, Dawit (Research on World Agricultural Economy, 2022)
Korarima is a known cash crop in the South Omo zone and provides a wide range of economic and sociocultural benefits. Even though its economic and socio-cultural importance, the development of the Korarima sector along with the value chain is hampered by several constraints. Hence, the study aimed to analyze the Korarima value chain in the South Omo zone. Using a two-stage sampling technique, 120 Kororima producers were selected to collect primary data through structured questionnaires. Descriptive statistics and an econometrics model (multivariate probit model) were used for data analysis. The study identified three major Korarima market outlet choices as collectors, retailers, and wholesalers as alternatives to Korarima producers to sell the majority of their products. Thus, collectors accounted for 82.2%, wholesalers (73.6%), and retailers (35.5%) of the total sold. The results of a multivariate probit model indicated that the sex of the household, credit access, family size, price information, market distance, and extension contact of farmers significantly affected the market outlet choice decisions in one or another way. Furthermore, no brand indicating this crop, inadequate infrastructural development, and market accessibility, and weak extension services regarding improved varieties were major problems identified. Therefore, it is better to work on the brand name of this particular crop to trace up to the end market, infrastructural development and market accessibility, and extension services provided regarding the improved Korarima variety, and accessing formal market information from the concerned body are essential to enhance Korarima producers’ benefit and bargaining power through avoiding information asymmetry. ER